Modelagem fuzzy da dinâmica de cianobactérias e análise de risco ambiental em rios, utilizando parâmetros hidráulicos e de transporte de massa - Souza, Alice Rocha de (2016)
Excessive proliferation of phytoplanktonic organisms, a phenomenon known as flowering Or -bloom‖, with cyanobacteria being the most frequent organisms in water blooms Has been an environmental problem in the world. Several surveys have paid attention Especially to the occurrence of cyanobacteria, because some species are potential Toxins and may pose a serious health risk to the population. This job Developed an environmental risk analysis methodology related to the proliferation of Cyanobacteria in rivers, based on a fuzzy mathematical structure, so that models Can be evaluated. For the study, hydraulic models were developed Together with mass transport models for nutrients, making it possible to know the Behavior of the cyanobacteria in the movement and growth in rivers and, with this, Perform the fuzzy risk and reliability calculation. The model presents a Fuzzy mathematics, which describes the dynamics of cyanobacteria in terms of density, Growth, vertical and horizontal migration as a function of light, temperature, nutrients and Hydraulic fluvial, allowing to carry out environmental risk analysis according to the legislation. Simulations were performed through a computer program in language FORTRAN, on the influence of these environmental parameters on the water body and on the Cyanobacteria, both in the vertical and in the longitudinal direction of the river. The results Showed that among the evaluated parameters, the luminosity was the one that showed greater Influence on the behavior of cyanobacteria, with direct effects on density, Growth rate and fluctuation of cyanobacteria, especially in the period of greatest Solar incidence. Phosphorus, a limiting nutrient in the study, showed that in greater or lesser Intensity is decisive in the process of development of cyanobacteria and that even For different concentrations, have a behavior with very close variations, Providing similar behavior regarding cyanobacteria dynamics. With Temperature, the cyanobacteria showed better 26 ° C for all parameters studied, both vertically and horizontally River. Finally, the developed model proved to be a viable alternative in the risk assessment Of cyanobacteria in rivers, and can thus subsidize management actions and Monitoring of water quality.